Effect of Vagal Nerve Stimulation on Swallowing in Subjects with Post Stroke Dysphagia. - Prabhu R.; Kumaresan A.; Vishnuram, Surya; Suganthirababu, Prathap; Srinivasan, Vignesh; Kumar, Priyadharshini; Dhanusia S. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: The study was developed to find the effect of auricular transcutaneous vagal nerve stimulation on difficulty in swallowing in post stroke dysphagia. Purpose: The purpose of this research is to extensively investigate and analyse how VNS impacts swallowing in people with post-stroke dysphagia. Materials and Methods: A total, 30 individuals have been selected mainly according to the criteria of both the inclusion and exclusion, from the above-mentioned study setting. The study was explained to subjects and written consent was collected from all subjects prior to the initiation of procedure. The subjects included the study was randomly allocated into 2 groups The participants in group A will receive Transcutaneous auricular vagal nerve stimulation, which is given for 20 min with the frequency of about 25 Hz, amplitude: 1 mA, pulse width: 360 µs using clip electrode being placed in Cymba Concha, along with the conventional exercises and Group B will receive Neuromuscular electrical stimulation will be given as Interrupted direct current at 30 Hz for 100ms, and the intensity was increased until perceptible visible contraction. Results: Auricular transcutaneous vagal nerve stimulation showed a significant effect in improving swallowing functions at 4 weeks, with a p value which is < 0.001. Conclusion: This study showed that the transcutaneous auricular vagal nerve stimulation showed a positive effect in improving swallowing functions in patients with dysphagia.